2020
DOI: 10.1073/pnas.1919337117
|View full text |Cite
|
Sign up to set email alerts
|

Unsaturated nanoporomechanics

Abstract: Although some important advances in the modeling of sorption and hygrothermal deformations of nanoporous materials such as hydrated cement paste, shale, coal, and some other rocks and soils have already been made, a comprehensive nanoporomechanics theory remains elusive. Here we strive to formulate it based on Gibb’s free energy of the solid–fluid system and on the recently derived Nguyen–Rahimi–Bažant (NRB) isotherm, which corrects the Brunauer–Emmett–Teller (BET) isotherm for the effect of hindered adsorbed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 37 publications
0
12
0
Order By: Relevance
“…108 showed that the elastic modulus calculated from confined nitrogen in a range of pore sizes provides a linear trend as a function of the reciprocal pore size d −1 , see Figure 24 Wave propagation in fluid-saturated porous media has been studied within the theoretical framework of poromechanics, starting from the pioneering works by Biot [86,87], and many contributions by Coussy [166,167]. Later works by Coussy [168,169], as well as by Bažant [170] included extension of poroelasticity to nanoporous media, in particular taking into account the effects of adsorption. However, the change of compressibility of fluids as a result of confinement, and its effects on wave propagation have not been discussed in the poromechanics literature.…”
Section: Relating Experiments and Theorymentioning
confidence: 99%
“…108 showed that the elastic modulus calculated from confined nitrogen in a range of pore sizes provides a linear trend as a function of the reciprocal pore size d −1 , see Figure 24 Wave propagation in fluid-saturated porous media has been studied within the theoretical framework of poromechanics, starting from the pioneering works by Biot [86,87], and many contributions by Coussy [166,167]. Later works by Coussy [168,169], as well as by Bažant [170] included extension of poroelasticity to nanoporous media, in particular taking into account the effects of adsorption. However, the change of compressibility of fluids as a result of confinement, and its effects on wave propagation have not been discussed in the poromechanics literature.…”
Section: Relating Experiments and Theorymentioning
confidence: 99%
“…For instance, Bažant (1972) obtained an analytical expression of the hygrothermal coefficient by taking the derivative of BET sorption isotherm (Brunauer et al 1938) with respect to temperature. Later, in Nguyen et al (2020), the hygrothermal coefficient of cement pastes was derived from the GAB sorption isotherm (Anderson 1946) and the NRB sorption isotherm (Nguyen et al 2019). Radjy et al (2003) proposed an empirical expression for the hygrothermal coefficient based on their empirical equation for the enthalpy of adsorption.…”
Section: Introductionmentioning
confidence: 99%
“…C–S–H comprises approximately 60−70 wt.% of fully hydrated Portland cement and glues the cement grains and aggregates together. Over the years, it has been demonstrated that the nanoscale structure of C–S–H governs most of the properties of Portland cement concrete including strength and resistance to physical and chemical attack 6, 7 . C–S–H is also responsible for concrete's most complex properties, such as time‐dependent behaviors, like creep and drying shrinkage 6, 8 …”
Section: Introductionmentioning
confidence: 99%
“…6,7 C-S-H is also responsible for concrete's most complex properties, such as time-dependent behaviors, like creep and drying shrinkage. 6,8 However, C-S-H is one of the most complex of all gels: its nanoscale structure has long eluded scientists in the F I G U R E 1 Stages of research on C-S-H, the main binder of Portland cement concrete. The knowledge of C-S-H's complex nanostructure evolved along with the development of characterization and simulation techniques and supported the uttermost goal of the field: the nanoengineering of C-S-H gel.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation